2003
DOI: 10.1191/0269215503cr612oa
|View full text |Cite
|
Sign up to set email alerts
|

Shoulder pain in people with a stroke: a population-based study

Abstract: Shoulder pain after stroke is common, especially in patients with severe sensorimotor deficits, diabetics and those living at home. Appropriate management may reduce the rate of occurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
103
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(119 citation statements)
references
References 12 publications
4
103
0
Order By: Relevance
“…Headache in the acute phase of stroke has been reported in 27-31% of patients, depending on the type of stroke (Vestergaard et al, 1993;Tentschert et al, 2005;Verdelho et al, 2008), whereas headache with late onset has shown prevalence rates of 3.5-11% within the first 2 years (Ferro et al, 1998;Widar et al, 2002;Jonsson et al, 2006). Shoulder pain has been reported in 15-40% of patients within 6 months after stroke (Langhorne et al, 2000;Gamble et al, 2002;Ratnasabapathy et al, 2003;Lindgren et al, 2007), and CPSP is seen in 5-11% of stroke patients (Andersen et al, 1995;Bowsher, 2001;Weimar et al, 2002;Widar et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Headache in the acute phase of stroke has been reported in 27-31% of patients, depending on the type of stroke (Vestergaard et al, 1993;Tentschert et al, 2005;Verdelho et al, 2008), whereas headache with late onset has shown prevalence rates of 3.5-11% within the first 2 years (Ferro et al, 1998;Widar et al, 2002;Jonsson et al, 2006). Shoulder pain has been reported in 15-40% of patients within 6 months after stroke (Langhorne et al, 2000;Gamble et al, 2002;Ratnasabapathy et al, 2003;Lindgren et al, 2007), and CPSP is seen in 5-11% of stroke patients (Andersen et al, 1995;Bowsher, 2001;Weimar et al, 2002;Widar et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…2 The cause of hemiplegic shoulder pain is multifactorial, 3,4 and contributions have been described from biomechanical changes, 1,5 spasticity, 6,7 and central-pain mechanisms. 8,9 Population based studies suggest that approximately one quarter of stroke survivors develop hemiplegic shoulder pain, 10,11 although higher rates of 52% to 54% have been reported in large studies using retrospective, 12 prospective, 13 and literature review 14 methodologies. Hemiplegic shoulder pain is associated with reduced functional ability, 15 a higher incidence of depression, 15 interference with rehabilitation, and an increased length of hospitalisation.…”
mentioning
confidence: 99%
“…1,2 The incidence varies between 9% and 40% depending on patient group and study design. [1][2][3][4] Different studies have used various terms for shoulder pain, eg, shoulder pain in hemiplegia, [5][6][7][8] hemiplegic shoulder pain, 9 and poststroke shoulder pain. 4 Sometimes, it is unclear whether only proximal pain in the arm was assessed or if also more distal arm pain was included.…”
mentioning
confidence: 99%
“…10 Shoulder pain hinders rehabilitation, is an important contributor to length of hospital stay, 11 and has been associated with depression 4 and decreased quality of life. 12 Several factors have been related to shoulder pain after stroke such as paralysis, 3,4,13,14 restricted range of motion in the shoulder, 5,6,13 spasticity, 7,8 right hemispheric cerebrovascular lesion and left hemiplegia, 6,8 sensory abnormalities, 4,8 diabetes mellitus, 3 low Barthel Index score, 11 and inappropriate handling of the patient. 9 Recovery from shoulder pain may occur in 80%.…”
mentioning
confidence: 99%